2022
DOI: 10.1007/s10964-022-01648-8
|View full text |Cite
|
Sign up to set email alerts
|

Living with COVID-19: Subjective Well-Being in the Second Phase of the Pandemic

Abstract: While there is ample evidence of the decline in mental health among youth during the onset of the COVID-19 pandemic, less is known about the determinants of recovery, which is the focus of this study. Drawing on a stress process framework, this study examines the associations of changes in direct, pandemic-related, and indirect, lockdown-related stressors with life satisfaction. A novel representative, longitudinal sample of British 16–25-year-olds is used, drawing on 6 data collections between February 2021 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…Thus, our study filled a knowledge gap by offering a wider perspective that considered macro and micro levels factors associated with generalized anxiety disorder among AYA. The literature on the global prevalence and burden of anxiety during COVID-19 pandemic showed a greater change in anxiety levels in younger ages compared to adults, and a stronger effect of the pandemic on adolescents’ mental health [ 31 , 32 , 33 ] reinforcing the importance of this study. Differences among countries in healthcare system structure, healthcare seeking behaviors stigmatization of mental problems and others are complex factors that need to be comprehensively studied following the suggested associations observed in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…Thus, our study filled a knowledge gap by offering a wider perspective that considered macro and micro levels factors associated with generalized anxiety disorder among AYA. The literature on the global prevalence and burden of anxiety during COVID-19 pandemic showed a greater change in anxiety levels in younger ages compared to adults, and a stronger effect of the pandemic on adolescents’ mental health [ 31 , 32 , 33 ] reinforcing the importance of this study. Differences among countries in healthcare system structure, healthcare seeking behaviors stigmatization of mental problems and others are complex factors that need to be comprehensively studied following the suggested associations observed in the present study.…”
Section: Discussionmentioning
confidence: 71%
“…However, even at this stage, some researchers felt that such concerns were overstated, and that even if an increase in distress or unhappiness was observed, it was likely to vary markedly across populations, and to reflect the combined influence of baseline social and economic factors alongside pandemic-related factors ( Rose et al, 2020 ). The subsequent course of events has tended to support the latter view: deteriorations in mental health status have been far from uniform ( Shevlin et al, 2021 ), and increases in life satisfaction and happiness have been reported from diverse geographical regions, particularly in the later stages of the pandemic ( Greyling et al, 2021 ; Gutierrez-Cobo et al, 2021 ; Henseke et al, 2022 ; Kimura et al, 2022 ; Paz et al, 2022 ). Moreover, it was observed that in certain settings, individuals came to value the interpersonal or relational dimension of happiness to a greater extent than they did pre-pandemic ( Bimonte et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we examined the prediction accuracy of the machine learning model using the top two and four features. Third, we conducted a multivariate logistic regression analysis to account for potential differences in perceptions of well-being based on gestation weeks [12], maternal age [25], parity [12], education level [4], and the presence of mental illness [7], as well as possible regional differences in the prevalence of COVID-19. We set the threshold age for the period as ≥35 years, which is generally considered the age of geriatric pregnancies [26].…”
Section: Sensitivity Analysesmentioning
confidence: 99%
“…Multiple studies have reported mixed evidence of the impact of the pandemic on the mental health of the general public [1,2]. Being a young woman may increase the likelihood of adverse mental health outcomes [1,3,4]. In addition, the isolation associated with the pandemic and changes in working styles, such as increased remote working, may have altered individuals' stress responses and allowed them to spend more time with their families [5][6][7].…”
Section: Introductionmentioning
confidence: 99%